What did Alumni Relations during the COVID-19 Lockdown look like? - Gallo, Maria L. (ICAReAlumni Conference Proceedings, 2020)
The COVID-19 pandemic thrust the world into lockdown in March 2020. People found themselves at home, with offices, schools and universities all closed as an attempt to contain the spread of the virus. As with many sectors, alumni relations within universities needed to reinvent itself. With relationship building at the core of its work, alumni relations had to reconsider new ways to engage and involve alumni. This paper outlines a very small-scale, short term study that stemmed from curiosity into a gathering of social media data, to observe how alumni relations offices communicated to the alumni base during this pandemic. Gathering evidence from 75 universities across 16 countries, the social media posts (Twitter, Facebook, LinkedIn, Instagram) relayed by alumni relations offices worldwide showed a broad base of activities, initiatives and information to alumni during the COVID-19 pandemic lockdown period in early 2020. Four key themes emerged from these social media posts: sharing, caring, daring and snaring, explained with examples in this article. The conclusion offers some comment on the state of alumni relations in universities, the ability for reinventing alumni engagement in a virtual way and the ability to offer a breadth of reliable information and opportunities for the benefit of alumni.